Effect of bio and organic fertilization on growth and production of Chrysanthemum (Chrysanthemum grandiflorum cv. Euro) . - نصور, مازن; كبيبو, عيسى; هديوه, حسام (Latakia University Journal -Biological Sciences Series, 2022)
The study was carried out in Lattakia, in cooperation by Department of Horticulture, and Department of soil and water sciences, Faculty of Agriculture, Tishreen University, during two seasons (2018-2019) and (2019-2020),the experiment was laid out in complete block design with three replications and five treatmeants (TO:control,T1: farmer,T2: organic fertilizer ,T3: bio-fertilizerS,T4: organic and bio-fertilizer).The aim of this study was to determine the role of bio and organic fertilization on vegetative growth and flowering of Chrysanthemum grandiflorum. Also investigating the ability of this bio and organic fertilization to provide nutrients for the plant in order to reduce the mineral fertilization. Bio fertilizer by EM1(2ml/m2) was applied tow times, one week after planting and one month after the first one. The results showed that the use of bio and organic fertilization (2kg/m2) had a positive effect on vegetative parameters (plant height and average number of leaves per plant, plant length, leaves area, chlorophyll content, proportion of dry matter and leaves content of some macro elements), and flowering parameters (flowers diameter, floral stem length, number of flowers on plant). The results also showed the positive impact of organic and bio fertilizer in some root parameters (size of roots, dry matter ratio).